Modeling Enhancements in Routing Protocols under Mobility and Scalability Constraints in VANETs. (3rd July 2014) - Javaid, N.; Akbar, M.; Khan, Z. A.; Alghamdi, T. A.; Saqib, M. N.; Khan, M. I.
Abstract : This paper presents mathematical framework for calculating transmission probability in IEEE 802.11 p based networks at Medium access control (MAC) layer, mathematical framework for calculating energy costs of the chosen routing protocols at network layer, and enhancements in optimized link state routing (OLSR), dynamic source routing, (DSR) and fish-eye state routing (FSR) to tackle delay in vehicular ad hoc networks (VANETs). Besides the enhancements, we analyze ad hoc ondemand distance vector (AODV) along with OLSR, DSR, and FSR as well. To evaluate the effect of our proposed transmission probabilities in the selected routing protocols, we choose network throughput, end-to-end delay (E2ED), and normalized routing load (NRL) as performance metrics. We also investigate the effect of different mobilities as well as scalabilities on the overall efficiency of the enhanced and default versions of the selected protocols. Simulations results which are conducted in NS-2 show that overall DSR-mod outperforms rest of the protocols.